Identification of clinical predictors for dupilumab dose spacing in adults with atopic dermatitis: a real-world study - Andrea Chiricozzi; Giacomo Dal Bello; Niccolò Gori; Lucia Di Nardo; Donatella Schena; Giacomo Caldarola; Martina Maurelli; Clara De Simone; Giampiero Girolomoni; Ketty Peris (Journal of Dermatological Treatment, 2023)
Background Dupilumab is a monoclonal antibody against the IL-4/IL-13 receptor-subunit approved for the treatment of moderate-severe atopic dermatitis (AD). Some attempts to increase dose interval have been described in both trial and real-world settings. Objective This study aimed to identify predictive clinical and demographic factors affecting patient selection for dose spacing or treatment withdrawal due to satisfactory response. Materials and methods This retrospective study included adult patients with moderate-to-severe AD treated with dupilumab for at least 16 weeks. Descriptive statistics were performed to analyze demographic and clinical variables. Logistic regression models were used to identify predictor variables. Results A total of 818 adult patients with moderate-to-severe AD was included in the study and 12% (97/818) of them performed dose spacing to 3–4 weeks or treatment withdrawal (8%, 67/818). The presence of non-cutaneous atopic manifestations (OR = 1.59, 95%CI = 1.06–2.38, p = 0.024), prurigo nodularis phenotype (OR = 4.5, 95%CI = 1.87–10.9, p = 0.001) and the age at treatment initiation (OR = 1.82, 95%CI = 1.12–2.94, p = 0.015) were confirmed as the strongest predictors of dose spacing or treatment withdrawal while maintaining dupilumab effectiveness. Conclusion Our findings contribute to define the patient profile that could maintain the therapeutic response after dose spacing or treatment withdrawal.